Ukraine during the Russian war of aggression: The nexus between internal developments and EU accession - Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2024)
The Russian war of aggression has deepened relations between the EU and Ukraine. This can be seen, above all, in Ukraine's EU candidate status. Despite the war, Ukraine continues to pursue many reforms, even if their pace has slowed since February 2022. The strong concentration of power in the Office of the President negatively affects the separation of powers. It makes judicial reforms more difficult and hinders parliament's ability to exercise its functions. The war has weakened the power of oligarchs in Ukraine in many respects. Yet the form of governance in the country has not experienced a clear break from the past. Even during the invasion, the authorities are continuing their fight against corruption among the elite. The population perceives some progress, but high-level corruption remains a deep-rooted challenge. Civil society activities have changed both qualitatively and quantitatively as a result of the war and have become more significant since the invasion. Civil society engagement can be fostered with the help of returning Ukrainian migrants and through the involvement of Ukrainians abroad. Ukraine's municipalities will play a key role in reconstruction, or are doing so already. To ensure that reconstruction is successful in all its dimensions, municipalities should continuously be involved in the mechanisms and processes currently being developed. In order to meaningfully intensify Ukraine-EU relations, it is essential that rule of law be expanded and consolidated, not only in Ukraine, but also in the EU and its member states.
Keywords: 320; Russian war of aggression; EU; Ukraine; Office of the President; separation of powers; judicial reforms; power of oligarchs; corruption among the elite; civil society engagement; municipalities; reconstruction; rule of law